The Maqasid Al-Shariah Model and Its Application in Islamic Banking: An Analysis From Scholars And Academics Perspective - Ramdani Harahap, Soritua Ahmad; Maulana, Hartomi; Maemunah, Hayatul; Rahmadani, Muhammad Rizky (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa, 2024)
Islamic banking is struggling in maintaining it in the financial industry by adhering to sharia principles. The development of Islamic banking continues to increase, starting from the performance, products, and other services. However, there are some problems in Islamic banking such as the murobahah financing which still supports the approval of Islamic banking and the lack of public understanding of about Islamic finance products. The research method used in this study through a qualitative approach to the form of stages of observation, interviews with practitioners and academics to complete the data and data documentation. To achieve valid results, interviews were conducted using purposive sampling techniques. This research reveals that in general the main purpose of maqāṣid al-sharī‘ah according to the agreement of the scholars is to achieve maslahah. To see the above, the maqāṣid al-sharī‘ah model is one model that can measure the performance of Islamic banking with a conception based on Islamic scholars. The three main points that become aspects of the benchmark are Tahdhib al-Fard (Educating individuals), Iqamah al-`Adl (Establishing justice) and Jalb al-Maslahah (Promoting Welfare).